Kebijakan Revaluasi Aktiva Tetap dalam Strategi Perpajakan dan Rasio Debt to Equity Ratio ( Studi Kasus PT Pecete) - Murifal, Badar; Suhartono, Suhartono (www.bsi.ac.id, 2019)
Abstract – The use of historical value (acquisition price) makes the asset value lose its relevance because it does not reflect the current value so it needs to be read carefully. Some credit analysts request appraisal assistance to reassess fixed assets if they are to be used to determine the amount of credit and the feasibility of the entity to receive credit. But historical values have advantages in terms of reliability. Historical value is based on the acquisition price at the time of purchase so that the evidence and its value can be verified. While the fair value or current value for fixed assets is not easily obtained because there is no active market price for fixed assets. If determined by the company allows bias in the assessment. Appraisal assessments can provide mixed results if the assumptions used are different. To avoid the value of assets still losing relevance, a company can revaluate its fixed assets by following the regulations that apply according to PSAK, its laws and regulations regarding taxation and regulations from the decisions of the finance minister. Revaluation is one method of valuing fixed assets. If an entity chooses to use the revaluation method, this method must be applied consistently by the company. Companies may not only use the occasional revaluation method for the purposes mentioned above, but the revaluation must be carried out regularly.